(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The article is devoted to the modernization of preschool education spiritual and moral ducation and development of a child of preschool age. The article analyzes the problems, explains the possibilities of their successful solution precisely in preschool childhood; reveals the tasks, principles, content, forms and methods of developing interaction between adults and children, aimed at the spiritual and moral development of preschoolers, and the possible positive results of this activity.